Ecological Park with a Sustainable Approach for the Revaluation of the Cultural and Historical Landscape of Pueblo Libre, Peru—2023 - Diego C. Mancilla-Bravo; Vivian M. Chichipe-Mondragón; Doris Esenarro Vargas; Cecilia Uribe Quiroz; Dante Calderón Huamaní; Elvira Ruiz Reyes; Crayla Alfaro; Maria Veliz (Clean Technologies, 2025)
Lack of green spaces, citizen insecurity, and crime are the primary issues afflicting the Pueblo Libre district. This research aims to propose public spaces that revalue the cultural and historical landscape of Pueblo Libre. The methodology involves a literature review, urban analysis, and climate analysis, incorporating sustainability strategies supported by digital tools (AutoCAD, Revit, and Sketch-Up). The resulting design features an ecological park with vegetation capable of capturing carbon and emitting oxygen, absorbing up to 3544.99 kg of CO2 annually. It also includes installing 26 solar-powered lights to illuminate necessary spaces efficiently and using eco-friendly materials. Additionally, the park incorporates an artificial wetland with a capacity to process 38,500 L of water using plants that remove toxic elements and capture nutrients. In conclusion, the ecological park seeks to revalue the cultural landscape and counteract environmental degradation by creating a green lung that purifies the air, fosters social connectivity, and integrates users with nature, enhancing their quality of life.